In brain mitochondria the branched-chain fatty acid phytanic acid impairs energy transduction and sensitizes for permeability transition - SCHöNFELD, Peter (Portland Press Ltd., 2004)
Phytanic acid (3,7,11,15-tetramethylhexadecanoic acid) accumulates at high levels throughout the body in the adult form of Refsum disease, a peroxisomal genetic disorder. However, it is still unclear why increased levels of phytanic acid have cytotoxic effects. In the present study, we examined the influence of non-esterified phytanic acid on energy-related functions of mitochondria from adult rat brain. Phytanic acid at low concentrations (5–20 μM, i.e. 5–20 nmol/mg of mitochondrial protein) de-energized mitochondria, as indicated by depolarization, stimulation of non-phosphorylating oxygen uptake and inhibition of the reduction of the tetrazolium dye 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide. The unbranched homologue palmitic acid exerted much smaller effects. In addition, phytanic acid reduced state 3 respiration, which was partly due to inhibition of the ADP/ATP carrier. Phytanic acid decreased the rate of adenine nucleotide exchange and increased the degree of control, which the ADP/ATP carrier has on state 3 respiration. Important for functional consequences is the finding that mitochondria, which are preloaded with small amounts of Ca(2+) (100 nmol/mg of protein), became highly sensitized to rapid permeability transition even when only low concentrations of phytanic acid (below 5 μM) were applied. In conclusion, the incorporation of phytanic acid into the inner mitochondrial membrane increases the membrane H(+) conductance and disturbs the protein-linked functions in energy coupling. This is most probably essential for the short-term toxicity of phytanic acid. Thus in neural tissue, which becomes enriched with phytanic acid, the reduction in mitochondrial ATP supply and the facilitation of the opening of the permeability transition pore are two major mechanisms by which the branched-chain fatty acid phytanic acid induces the onset of degenerative processes.